Female mice exhibit resistance to disease progression despite early pathology in a transgenic mouse model inoculated with alpha-synuclein fibrils - Stephanie Tullo; Janice Sung Hyun Park; Daniel Gallino; Megan Park; Kristie Mar; Vladislav Novikov; Rodrigo Sandoval Contreras; Raihaan Patel; Esther del Cid-Pellitero; Edward A. Fon; Wen Luo; Irina Shlaifer; et al. (Communications Biology)
Abstract Despite known sex differences in human synucleinopathies such as Parkinson’s disease, the impact of sex on alpha-synuclein pathology in mouse models has been largely overlooked. To address this need, we examine sex differences in whole brain signatures of neurodegeneration due to aSyn toxicity in the M83 mouse model using longitudinal magnetic resonance imaging (MRI; T1-weighted; 100 μm3 isotropic voxel; -7, 30, 90 and 120 days post-injection [dpi]; n ≥ 8 mice/group/sex/time point). To initiate aSyn spreading, M83 mice are inoculated with recombinant human aSyn preformed fibrils (Hu-PFF) or phosphate buffered saline in the right striatum. We observe more aggressive neurodegenerative profiles over time for male Hu-PFF-injected mice when examining voxel-wise trajectories. However, at 90 dpi, we observe widespread patterns of neurodegeneration in the female Hu-PFF-injected mice. These differences are not accompanied by any differences in motor symptom onset between the sexes. However, male Hu-PFF-injected mice reached their humane endpoint sooner. These findings suggest that post-motor symptom onset, despite accelerated disease trajectories for male Hu-PFF-injected mice, neurodegeneration may appear sooner in the female Hu-PFF-injected mice (prior to motor symptomatology). These findings suggest that sex-specific synucleinopathy phenotypes urgently need to be considered to improve our understanding of neuroprotective and neurodegenerative mechanisms.